Incidencia del clima laboral en el desempeño del personal de la Dirección Distrital de Educación 13D06 Junín – Bolívar 2022 - Araujo Anchundia, Julissa Katherine (2023)
The present research work was prepared with the purpose of analyzing the incidence of the work environment in the performance of the personnel of the District Directorate of Education 13D06 Junín - Bolívar 2022. The methodology used in this non-experimental investigation was the inductive method, deductive and analytical. The research techniques that were applied to collect the information was the survey, which was applied to the administrative staff of the District Directorate of Education 13D06 Junín - Bolívar; and for its interpretation, the Ishikawa diagram and the 5w+1H matrix were used, the results of which revealed the level of work environment in administrative personnel; on the other hand, the interview was also carried out, which was addressed to the departmental director of said institution, results were obtained that radiate a level of moderate work environment, although it usually changes, due to existing problems such as the lack of performance evaluations, the inappropriate management of the warehouse, discomfort of its facilities and the lack of training in professional development, causing low work performance and also reflecting on the health of employees; that is why a matrix was created as a strategy in order to reduce the negative aspects of the work environment and improve work performance in its servers.